Incidence and pattern of dental emergencies and their management during Covid-19 pandemic : An experience of Nepali dentists working during lock down (Orthodontic Journal of Nepal, 2020)
Introduction: Corona Virus Disease-2019 (COVID-19) is highly contagious nature of disease which has spread all over the world in short span of time leading to significant number of death. WHO has declared pandemic and every nation is fighting with their all possible resources to control this disease. The impact of COVID-19 in dentistry is enormous. Most of the dental hospitals and clinic are providing emergency dental services only. So the aim of this research is to find out the nature of dental emergency during the initial month of lock down in Nepal. Additionally this research will try to find out the number of dental emergencies as well as perception of dentists on impact of COVID-19 on dentistry.Materials and Method : A set of electronic questionnaires were sent to 150 Nepal Medical Council registered Nepalese dentists out of which only 122 dentists responded. A consent was obtained prior to collecting data for research purpose. All the quantitative answers were recorded in SPSS spread sheet where as qualitative data were collected in Microsoft word. Descriptive statistics were applied to explain the responses whenever applicable.Result: Out of 122 respondents, maximum were from province 3 and 4 (50% and 34%). Almost half of the respondents were general dental practioners and similar percentage of respondents were working at dental/medical colleges and government centers. 90% of the doctors had consulted patients during lock down period. Average 5-20 cases were seen during the lock down by majority of doctors. Nearly 58% of the doctors had done only virtual consultation and most common emergency was dental pain(n= 92) and swelling( n= 37). Majority of the respondents thought that standard of dental disinfection and sterilization will increase after pandemic, however most of the dentists thought they will be using PPE for dental work and cost of dental treatment will be increased because of the added cost of extra precaution. 90% of the dentists believed that they are going to change the way they practice dentistry after they reopen their clinic.Conclusion: The most common type of dental emergency during lock down is dental pain ,swelling, dento-maxillofacial trauma and broken orthodontic appliances. Virtual dental consultation is gaining popularity among dentists in Nepal and Nepalese dentists are going to change the way of dental practice because of COVID-19.